2013
DOI: 10.3109/17453674.2013.850013
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy with polidocanol for treatment of aneurysmal bone cysts

Abstract: Background and purposeRecent data suggest that percutaneous sclerotherapy is a safe alternative to surgery for treatment of aneurysmal bone cysts (ABCs). We present our experience of this method.MethodsWe retrospectively analyzed data from 38 consecutive patients treated with repeated injections of polidocanol. Each injection consisted of 2–4 mg polidocanol per kg body weight. Radiological and clinical assessments were performed until healing.ResultsAll cycts except 1 healed after a median of 4 (1–11) injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 17 publications
0
60
0
14
Order By: Relevance
“…Recent publications on minimally-invasive techniques (e. g. injection of fibrosing agents or CT-guided injection of demineralized bone and bone marrow) demonstrate that extensive operations can be avoided [2, 16, 27 -29]. Likewise, percutaneous injection of polidocanol for sclerotherapy of the cyst is an effective procedure; however, in the case of larger cysts, multiple applications using anesthesia are required [13]. Sequential injection therapy in the sacral region can be usefully employed, especially if angiography rules out a hypervascularized tumor bed, and embolization does not appear to be medically sensible.…”
Section: Clinical Post-treatment Examinationmentioning
confidence: 99%
“…Recent publications on minimally-invasive techniques (e. g. injection of fibrosing agents or CT-guided injection of demineralized bone and bone marrow) demonstrate that extensive operations can be avoided [2, 16, 27 -29]. Likewise, percutaneous injection of polidocanol for sclerotherapy of the cyst is an effective procedure; however, in the case of larger cysts, multiple applications using anesthesia are required [13]. Sequential injection therapy in the sacral region can be usefully employed, especially if angiography rules out a hypervascularized tumor bed, and embolization does not appear to be medically sensible.…”
Section: Clinical Post-treatment Examinationmentioning
confidence: 99%
“…Eine weitere minimal-invasive Modalität für die Behandlung von AKZ, welche in den letzten Jahren an Bedeutung zugenommen hat, ist die perkutane Instillation von Polidocanol, einer sklerosierenden Substanz, die zur Therapie oberflächlicher Varizen eingesetzt wird [4,19,24]. Ziel der Behandlung ist die Denaturierung der Zys tenwand, die zur ossären Konsolidierung führt (.…”
Section: Polidocanolinstillationunclassified
“…1, [19]). Auch dieses Verfahren wird nur bei primären AKZ nach histologischer Sicherung angewendet [4,19,24]. Da im Moment der Polidocanolinstillation kurzzeitig starke lokale Schmerzen auftreten können, findet die Intervention in Allgemeinnarkose oder Analgosedierung statt [4,19].…”
Section: Polidocanolinstillationunclassified
“…Adjuvant radiation has been associated with malignant transformation and is therefore not recommended; however, cases have progressed to malignancy without prior radiation [50] . Sclerotherapy is an alternative with relative success for aneurysmal bone cysts not amenable to surgical treatment, although we cannot find a case of sclerotherapy for an orbital lesion [51,52] . Recently, Pelle et al [53] have demonstrated strong RANK ligand expression in stromal cells in vivo and tumor shrinkage in a 5-year-old boy with a large sacral aneurysmal bone cyst treated with denosumab [54] .…”
Section: Benign Reactive Bone Lesions Of the Orbitmentioning
confidence: 99%